2008
DOI: 10.4103/0019-5278.40815
|View full text |Cite
|
Sign up to set email alerts
|

Mental stress in the workers exposed to humidity in a cheese processing factory

Abstract: Certain inevitable physical factors in working environment can damage the workers in related fields. Sea sickness and white finger due to ship movement and vibration respectively are two examples in this regard. Humidity in working area can also bring discomfort of the workers in humid area. Cheese processing factories are such places where there is high humidity in the working space.Mental stress is a psychological complication which can arise due to some physical factors in certain occupational activities, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Humidity is another stressor that affects the mental health of people. Shushtarian et al [ 19 ] evaluated these effects. The results showed that workers who were exposed to higher humidity environments had higher stress levels compared to other workers.…”
Section: Related Workmentioning
confidence: 99%
“…Humidity is another stressor that affects the mental health of people. Shushtarian et al [ 19 ] evaluated these effects. The results showed that workers who were exposed to higher humidity environments had higher stress levels compared to other workers.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, the humidity in some occupational activities is unavoidable and this physical factor is reported to produce mental stress in workers of a cheese-processing factory. [ 1 ] On the other hand, most of the hazardous agents can be controlled to protect the workers in different factories. Intraocular foreign bodies (IOFB) produced by hammering or chiseling can damage the visual system of the workers in related fields.…”
Section: Introductionmentioning
confidence: 99%